Determination of Clinical, Electrophysiological, and Radiological Characteristics of Pediatric Autoimmune Encephalopathy - Güngör, Mesut; Öztürk, Merve; Deniz, Adnan; Alikılıç, Defne; Karaca, Ömer; Anık, Yonca; Kara, Bülent (Journal of Pediatric Neurology, 2023)
Autoimmune encephalopathy (AE) is a group of diseases with subacute onset, that represents a wide clinical spectrum, manifested by complex neuropsychiatric symptoms and signs. In this study, the data of 27 patients diagnosed and followed up in our clinic with the diagnosis of AE between 2011 and 2021 were evaluated retrospectively. Out of 27 patients, 6 were definite seropositive AE, 2 of them met the diagnostic criteria for limbic encephalitis, and the remaining 19 were probable AE. Nowadays, we see AEs with increasing frequency. While there is a generally established approach in the diagnosis and treatment of seropositive patients, there are still hesitations and diagnostic difficulties in seronegative AEs. In this study, clinical, radiological, and prognostic features of definite and probable AE patients diagnosed in a tertiary pediatric neurology clinic were documented. It is thought that pediatric neurologists have an important responsibility to increase awareness about AE in pediatricians. In the future, it is predicted that AE will be diagnosed more frequently with new antibodies and one has to differentiate it from viral encephalitis and neuropsychiatric syndromes and diseases.
Keywords: autoimmune encephalopathy; limbic encephalitis; anti-NMDA antibody